2020
DOI: 10.24093/awej/call6.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Whiteboard Animation in Project-Based Learning on Indonesian EFL Students’ English Presentation Skills across Creativity Levels

Abstract: Technology has big roles in this 4.0 era. It can be applied effectively in the teaching and learning process. This article examines the effect of applying whiteboard animation in project-based learning (PjBL) on English as a Foreign Llanguage (EFL) students' English presentation skills, investigates whether the English presentation skills of EFL students who were taught by using whiteboard animation in PjBL differ significantly across creativity levels, and finds out whether there is interaction or not between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The author also reports how students' writing of video scripts has improved their linguistic skills in addition to developing their oral presentation skills, teamwork, and their organization and planning skills. Several other studies in EFL contexts reported similar benefits (Suhroh et al, 2020;Shaalan, 2020;Sirisrimangkorn, 2018).…”
Section: Studies Examining Pbl In Learning/teaching In Higher Educationsupporting
confidence: 52%
“…The author also reports how students' writing of video scripts has improved their linguistic skills in addition to developing their oral presentation skills, teamwork, and their organization and planning skills. Several other studies in EFL contexts reported similar benefits (Suhroh et al, 2020;Shaalan, 2020;Sirisrimangkorn, 2018).…”
Section: Studies Examining Pbl In Learning/teaching In Higher Educationsupporting
confidence: 52%
“…First studies were only able to show that whiteboard animations unfold positive effects on learning compared to other instructional formats ([ 15 ]), making a comparison that is confounded. Other studies have shown that such animations can be embedded in flipped classrooms or project-based learning settings ([ 16 , 18 ]) without losing the learning effect. Addressing this research gap, the goal of the two studies reported was the first experimental verification of two important factors (presentation mode and narrative context) implemented in whiteboard animations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, students who watched the animation before the tutorials performed better on the learning test than those who did not. In a study by Suhroh et al [ 18 ], whiteboard animations were implemented in a project-based learning setting. Hereby, students were asked to create such an animation as a part of a presentation while the control group only relied on traditional media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same way, Praba et al, (2018) also proclaimed that Indonesian EFL learners could significantly nourish their positive L2 writing learning behavior in the support of problem-based learning activities tangibly resulted in the striking enhancement of writing competencies. Dewi (2020); Hussein (2014); Kurniawati et al, (2019); Anggiati, Riswandi, and Sugiman (2018); Sholikhah (2019); Suhroh et al, (2020); Sukerti and Susana (2019); Wahyudin (2017);Wuryantari et al, (2019).…”
Section: Findings and Discussionmentioning
confidence: 99%